Vaccines for preventing influenza in healthy children. - Smith, S; Demicheli, V; Di Pietrantonj, C; Harnden, A; Jefferson, T; Matheson, N; Rivetti, A (2006)
BACKGROUND: In children and adults the consequences of influenza are mainly absences from school and work, however the risk of complications is greatest in children and people over 65 years old. OBJECTIVES: To appraise all comparative studies evaluating the effects of influenza vaccines in healthy children; assess vaccine efficacy (prevention of confirmed influenza) and effectiveness (prevention of influenza-like illness) and document adverse events associated with receiving influenza vaccines. SEARCH STRATEGY: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library Issue 1, 2005); OLD MEDLINE (1966 to 1969); MEDLINE (1969 to December 2004); EMBASE (1974 to December 2004); Biological Abstracts (1969 to December 2004); and Science Citation Index (1974 to December 2004). We wrote to vaccine manufacturers and a number of corresponding authors of studies in the review. SELECTION CRITERIA: Any randomised controlled trials (RCTs), cohort and case-control studies of any influenza vaccine in healthy children under 16 years old. DATA COLLECTION AND ANALYSIS: Two authors independently assessed trial quality and extracted data. MAIN RESULTS: Fifty-one studies involving 263,987 children were included. Seventeen papers were translated from Russian. Fourteen RCTs and 11 cohort studies were included in the analysis of vaccine efficacy and effectiveness. From RCTs, live vaccines showed an efficacy of 79% (95% confidence interval (CI) 48% to 92%) and an effectiveness of 33% (95% CI 28% to 38%) in children older than two years compared with placebo or no intervention. Inactivated vaccines had a lower efficacy of 59% (95% CI 41% to 71%) than live vaccines but similar effectiveness: 36% (95% CI 24% to 46%). In children under two, the efficacy of inactivated vaccine was similar to placebo. Thirty-four reports containing safety outcomes were included, 22 including live vaccines, 8 inactivated vaccines and 4 both types. The most commonly presented short-term outcomes were temperature and local reactions. The variability in design of studies and presentation of data was such that meta-analysis of safety outcome data was not feasible. AUTHORS' CONCLUSIONS: Influenza vaccines are efficacious in children older than two years but little evidence is available for children under two. There was a marked difference between vaccine efficacy and effectiveness. That no safety comparisons could be carried out emphasizes the need for standardisation of methods and presentation of vaccine safety data in future studies. It was surprising to find only one study of inactivated vaccine in children under two years, given recent recommendations to vaccinate healthy children from six months old in the USA and Canada. If immunisation in children is to be recommended as public-health policy, large-scale studies assessing important outcomes and directly comparing vaccine types are urgently required.